2022
DOI: 10.3390/healthcare10122415
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Vitamin and Mineral Deficiencies and High Levels of Non-Essential Heavy Metals in Saudi Arabian Adults

Abstract: Although the micronutrient status of a population is of high national priority, as it critically impacts public health, limited data is available for quantifying the micronutrient status in Saudi Arabia. We aimed to provide comprehensive, epidemiological, descriptive data regarding micronutrient levels in Saudi adults. This cross-sectional study included 3432 adults aged ≥ 18 years (mean age, 37.7 ± 11.7 years; women, 51.2%) across all 13 Saudi administrative regions (March 2019–November 2021). Laboratory data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
1
3
1
Order By: Relevance
“…Furthermore, 61.1% presented with a low level (23%) or an intermediate level (38.1%). When compared to other studies, regionally, the prevalence of low levels appeared to be higher in Jordan (30.1%) [51] and Iran (27.1%) [34] but lower in Saudi Arabia (7.5%) [52] than our study finding (23%). Internationally, all studies except India (34%) [46] reported a lower prevalence of low serum levels of B12, including Bangladesh (~<15%) [53], Liechtenstein (13.4%) [54], Panama (11.8%) [55], Spain (10.9%) [43], Costa Rica (11.2%) [56], the UK (6%) [42], Ireland (6%) [57], Canada (~<6%) [58], Ecuador (5.46%) [39], the US (~3-4% in 1999-2002 [41] and ~<7% in 2003-2006 [59]), France (3.3%) [60], Australia (2.3%) [61], and Korea (~<2%) [62].…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…Furthermore, 61.1% presented with a low level (23%) or an intermediate level (38.1%). When compared to other studies, regionally, the prevalence of low levels appeared to be higher in Jordan (30.1%) [51] and Iran (27.1%) [34] but lower in Saudi Arabia (7.5%) [52] than our study finding (23%). Internationally, all studies except India (34%) [46] reported a lower prevalence of low serum levels of B12, including Bangladesh (~<15%) [53], Liechtenstein (13.4%) [54], Panama (11.8%) [55], Spain (10.9%) [43], Costa Rica (11.2%) [56], the UK (6%) [42], Ireland (6%) [57], Canada (~<6%) [58], Ecuador (5.46%) [39], the US (~3-4% in 1999-2002 [41] and ~<7% in 2003-2006 [59]), France (3.3%) [60], Australia (2.3%) [61], and Korea (~<2%) [62].…”
Section: Discussioncontrasting
confidence: 94%
“…Furthermore, the most participants with low serum levels of B12 in the current study were females (68.6%), which was expected given the lower dietary B12 intake of females compared to males. The results from some studies aligned with ours [52][53][54], while others found a higher prevalence of low serum levels of B12 in males [73]. In short, females in Lebanon were found to be susceptible to low dietary intake and low serum levels of B12 in our population, presumably due to altered dietary patterns.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These findings suggest that alkaline-promoting diets tend to meet the Dietary Guidelines for Americans Guidelines’ recommendations on some macronutrients. Another study by Albalawi et al [ 7 ] examined the prevalence of micronutrients and arsenic levels among individuals in Saudi Arabia. The study reported that among the 14 micronutrients, adults in the sample were more deficient in vitamin D (64.3%).…”
Section: Nutrition Securitymentioning
confidence: 99%
“…In their study, Albawi et al [ 52 ] investigated the occurrence of vitamin and mineral deficiencies, as well as excessive levels of non-essential heavy metals, among adults in Saudi Arabia. The incidence of vitamin D deficiency exhibited variations based on age.…”
Section: Introductionmentioning
confidence: 99%